The Exclusionary Rule in Historical Perspective: The Struggle to Make the Fourth Amendment More than 'An Empty Blessing' - Kamisar, Yale (1979)
In the 65 years since the Supreme Court adopted the exclusionary rule, few critics have attacked it with as much vigor and on as many fronts as did Judge Malcolm Wilkey in his recent Judicature article, The exclusionary rule: why suppress valid evidence? (November 1978)